The Nexus Between Equitable Land Distribution and Poverty Reduction: An Overview of the Zimbabwean Situation - Percyslage Chigora (Elsevier, 2022)
Developments in Zimbabwe at the turn of the new millennium have been characterised by efforts to ensure that the land redistribution exercise takes place across all communities. This was done at a faster rate than witnessed anywhere in the world for the past two decades. The overall aim was to grapple with the rising levels of poverty and unemployment that led to discontent among the populace. Land redistribution represents the desire to increase participation in agricultural activities and place land in the hands of those who till the land. Economically, land redistribution makes a great deal of sense as it leads to a redistribution of income in favour of groups who are expected to spend their money on the domestic rather than international markets. The aim of this paper is to examine the linkage between inequitable land distribution and the socio-economic deprivations underlying poverty in Zimbabwe. The need to investigate arises from the standpoint that other societies have seen the gaps between the rich and the poor closing but having sought other models of reducing poverty other than of land redistribution. The examination provides a basis upon which justification for land reform can be carried out in some developing countries with similar land ownership patterns as in Zimbabwe in the pre-fast track land reform era. It also forms the basis upon which poverty can be reduced. The paper unearths controversies surrounding land reform, to be specific, the fast track land reform and its concerns the poor in Zimbabwe.